Associations of Parents’ Self, Child, and Other “Fat Talk” with Child Eating Behaviors and Weight - Lydecker, Janet A. (Int J Eat Disord, 2018)
OBJECTIVE: Fat talk—negative communication about weight—is common in the media, peer groups, and families. Little is known about parental fat talk directed at oneself or others. This study examined associations between different forms of parental fat talk and child disordered eating behaviors and weight, and differences by child sex and age. METHODS: Parents of pre-adolescents or adolescents (N=581) reported fat talk about themselves (self-fat talk), others (obesity-fat talk) and their child (child-fat talk). RESULTS: 76.0% of parents reported regular self-fat talk in front of children, 51.5% reported obesity-fat talk and 43.6% reported child-fat talk. Fat talk did not differ significantly between parents of pre-adolescents and adolescents but was more common with sons than daughters. Of the three forms of fat talk, only child-fat talk was associated with all child eating and weight variables (binge eating, overeating, secretive eating, and overweight/obesity); associations were strongest for adolescent girls. Child sex was associated with secretive eating and overweight/obesity. CONCLUSIONS: Parents reported using different forms of fat talk frequently. Parent self- and obesity-fat talk were reported more frequently, but child-fat talk was the most strongly associated with children’s eating and weight. Because of associations with disordered eating behaviors, intervening to reduce fat talk might contribute to improving pediatric disordered eating and weight-related interventions.